(untitled) (Italian Review of Legal History, 2024)
The study focuses on a legal opinion (consilium) authored by the Perugian jurist Onofrio Bartolini, addressing a dispute over taxation between Castiglione and Arezzo during the 1370s. The crux of the matter revolved around a woman from Castiglione who married a citizen of Arezzo but retained ownership of immovable property in her hometown. Castiglione contended that the property fell under its direct tax (libra), while Arezzo argued that upon marriage, the wife ceased to be a citizen of Castiglione and became a citizen of Arezzo, thereby subjecting her property to Arezzo’s libra. Bartolini, drawing upon Bartolo’s principles regarding the citizenship of the mulier alibi nupta, concluded that the jurisdiction to tax lay with Castiglione, where the wife retained her citizenship.